2011
DOI: 10.1017/s1743921311028018
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Dynamics of Planets in P-Type Motion Around Binaries

Abstract: Abstract. Up to now, more than 500 extra-solar planets have been discovered. Many of these extrasolar systems consist of one star and only one giant planet. However, recently more and more different types of systems have become known, including also extrasolar planets in binaries. In our study, we will concentrate on such systems, since a large percentage of all G-M stars are expected to be part of binary or multiple stellar systems. Therefore, these kinds of systems are worthy of investigation in detail. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The dynamical stability of the first fitted planetary configurations (Beuermann et al 2010) were investigated with detailed N-body simulations by Funk et al (2011) andHorner et al (2012b) who found that some were unstable, whereas others were dynamically feasible. In the first fit, the outer planet's eccentricity was set to zero.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamical stability of the first fitted planetary configurations (Beuermann et al 2010) were investigated with detailed N-body simulations by Funk et al (2011) andHorner et al (2012b) who found that some were unstable, whereas others were dynamically feasible. In the first fit, the outer planet's eccentricity was set to zero.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed companions around HU Aqr have been studied in detail, and a series of studies have revealed them to be dynamically unfeasible (Horner et al 2011;Hinse et al 2012a;Wittenmyer et al 2012a;Funk et al 2011Funk et al , 2012Goździewski et al 2012). The same is true of HW Vir ) and NSVS 14256825 Hinse et al 2014).…”
Section: Introductionmentioning
confidence: 99%